Integration of the Simple Additive Weighting Method for Decision Support System Superior Fishery Products in Indramayu Regency - Fikri, Moh. Ali; Ahmad Lubis Ghozali; Riyan Farismana; Sonty Lena (Universitas Negeri Semarang, 2025)
This study develops a web-based information system to support the incubation of superior fishery product businesses in Indramayu Regency by integrating the Simple Additive Weighting (SAW) method as a decision support system (DSS) for collectors. The research is motivated by the limited market access faced by fish farmers in Indramayu and the dominance of intermediaries in the marketing chain, which reduces farmers' bargaining power. To address this issue, the system applies the SAW method to generate commodity recommendations based on several criteria, including price, production capacity, location, commodity type, and harvest time. The system was implemented as a web-based platform to facilitate digital interaction between collectors and fish farmers. System evaluation was conducted through functional testing and user satisfaction assessment. Black box testing on 53 system functions showed that all functions operated according to system requirements. In addition, a user satisfaction evaluation involving 12 respondents using a Likert scale questionnaire resulted in an average score of 85.00%, which falls into the “very good” category. The results indicate that the integration of the SAW method can provide objective commodity recommendations and improve the efficiency of commodity search processes for collectors. Furthermore, the developed platform facilitates faster interaction between collectors and fish farmers and supports the expansion of digital marketing networks for superior fishery products. This study contributes to the development of digital decision support systems to strengthen the fisheries business ecosystem at the regional level.